2020
DOI: 10.1002/fsn3.2012
|View full text |Cite
|
Sign up to set email alerts
|

The difference of regulatory effect of two Inonotus obliquus extracts on high‐fat diet mice in relation to the fatty acid elongation function of gut microbiota

Abstract: Obesity is a disease that causes metabolic disorders in the human body and is closely related to intestinal microbes. This experiment compares the therapeutic effects of two Inonotus obliquus extracts on high‐fat diet (HFD) mice and explores the effects and mechanisms of intestinal flora and its metabolites. The energy intake (EI), weight gain (BWG), fecal flora diversity, fecal and urine metabolites, and fecal triglycerides (TG) of mice were measured at 4 temporal points. We found that due to the difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…[ [18][19][20][21][22][23][24] Polyphenol Antioxidant [25] Triterpenoid Anticancer, anti-inflammatory, antiviral, and antioxidant [26][27][28][29][30] Melanin Antioxidant, anti-inflammatory, antiviral, hypolipidemic and immunomodulatory [24,[31][32][33][34] Polysaccharides are natural biopolymers that all living organisms have. And the diversity in monosaccharide composition and structure causes them to have different biological activities [35].…”
Section: Component Biological Activities Referencesmentioning
confidence: 99%
“…[ [18][19][20][21][22][23][24] Polyphenol Antioxidant [25] Triterpenoid Anticancer, anti-inflammatory, antiviral, and antioxidant [26][27][28][29][30] Melanin Antioxidant, anti-inflammatory, antiviral, hypolipidemic and immunomodulatory [24,[31][32][33][34] Polysaccharides are natural biopolymers that all living organisms have. And the diversity in monosaccharide composition and structure causes them to have different biological activities [35].…”
Section: Component Biological Activities Referencesmentioning
confidence: 99%
“…Accumulated evidence indicates that natural products and their bioactive components, which are macromolecular bioactive carbohydrates with several biological activities and a high potential application value in the pharmaceutical field, have attracted considerable attention owing to their diverse bioactivities ( Miaoyu Li et al, 2021 ). A series of clinical studies have demonstrated that polysaccharides from fungi possess antitumor, immunomodulatory, anti-inflammatory, antioxidant, anti-aging, anti-hepatitis, and anti-diabetes properties ( Hu et al, 2017 ; Yang et al, 2021 ; Yu et al, 2021 ). Research on gut microbiota has become increasing prevalent in recent years; animal guts contain a remarkable abundance of microorganisms that are intimately related and play a major role in maintaining overall health ( Pickard et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the polysaccharides from Inonotus obliquus exert certain biological activities, thereby allowing it to be used as a prebiotic to fight diseases such as diabetes, cancer and cardiovascular diseases ( 16 ). Previous research has already found that IOP could help alleviate acute endometritis ( 20 ) and improve the severity of both obesity ( 39 ) and chronic pancreatitis ( 40 ) by converting the diversity of intestinal flora to a healthier state and this, in turn, improves the antioxidant status, thereby reducing inflammation levels, and improving host metabolism ( 41 ).…”
Section: Discussionmentioning
confidence: 99%